2009
DOI: 10.1295/polymj.pj2007210
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Wholly Aromatic Polyketones

Abstract: The structural design strategy and the synthetic approaches for the wholly aromatic polyketones and the monomers are described. Electrophilic aromatic aroylation substitution polycondensation and aromatic coupling polycondensation have been investigated as synthetic routes for wholly aromatic polyketones by the author's group. Acyl-acceptant arene molecules as the electrophilic aromatic aroylation substitution polycondensation type monomers and the aromatic nuclei for bis(chlorobenzoylated) compounds as the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 125 publications
(120 reference statements)
0
20
0
Order By: Relevance
“…Thus, our next goal was the copolymerization of aryne equivalents with carbon monoxide to produce aromatic polyketones/polyketals. 97 Although aromatic polyketones, 98,99 bearing main chains consisting of alternating arylene and carbonyl groups, are important as superengineering plastics, 100102 the range of accessible ones is narrow. In particular, aromatic polyketones bearing o-arylene units have been elusive.…”
Section: Copolymerization Of Aryne Equivalents With Carbon Monoxidementioning
confidence: 99%
“…Thus, our next goal was the copolymerization of aryne equivalents with carbon monoxide to produce aromatic polyketones/polyketals. 97 Although aromatic polyketones, 98,99 bearing main chains consisting of alternating arylene and carbonyl groups, are important as superengineering plastics, 100102 the range of accessible ones is narrow. In particular, aromatic polyketones bearing o-arylene units have been elusive.…”
Section: Copolymerization Of Aryne Equivalents With Carbon Monoxidementioning
confidence: 99%
“…The latter is now the main method used, and is performed at high temperature (180 °C) in DMAc . The synthetic route involving the Friedel–Crafts polycondensation suffers from low reactivity and poor selectivity compared to nucleophilic aromatic substitution …”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] The synthetic route involving the Friedel-Crafts polycondensation suffers from low reactivity and poor selectivity compared to nucleophilic aromatic substitution. [ 11 ] A PEES copolymer in which double bonds were regularly inserted along the backbone was recently developed by our group, and can be synthesized either by using acyclic diene metathesis polymerization or regular polycondensation reaction. [ 12 ] This double bond is easily modifi ed, and can provide an alternate route to the direct modifi cation of PES on aromatic ring, [13][14][15][16] or to modifi cation via copolymerization with other polymeric blocks.…”
Section: Introductionmentioning
confidence: 99%
“…PEEK) suffer from poor creep behavior above their relatively low glass transitions, the synthesis of novel semicrystalline PAEKs with increased T g is of high interest. The introduction of a variety of stiff and bulky groups such as biphenyl or naphthalene into the polymer backbone is one of the common approaches for increasing T g because it offers good advantages concerning the stability and thermal resistance of the resulting polymer . The copolymerization of PEEK was also investigated in order to improve its glass transition temperature ( T g ), and processability at high temperatures, and to obtain low‐cost materials, but the improvement of T g is not so marked for those reported PEEK copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a variety of stiff and bulky groups such as biphenyl or naphthalene into the polymer backbone is one of the common approaches for increasing T g because it offers good advantages concerning the stability and thermal resistance of the resulting polymer. [24][25][26][27][28][29] The copolymerization of PEEK was also investigated in order to improve its glass transition temperature (T g ), and processability at high temperatures, and to obtain low-cost materials, [30][31][32][33] but the improvement of T g is not so marked for those reported PEEK copolymers. Shibata et al [34] reported the synthesis of the block copolymers of the PEEK and the poly(aryl ether sulfone) containing biphenylene moieties (PEBS).…”
Section: Introductionmentioning
confidence: 99%